2017
DOI: 10.3390/coatings7030045
|View full text |Cite
|
Sign up to set email alerts
|

Review of Antibacterial Activity of Titanium-Based Implants’ Surfaces Fabricated by Micro-Arc Oxidation

Abstract: Ti and its alloys are the most commonly-used materials for biomedical applications. However, bacterial infection after implant placement is still one of the significant rising complications. Therefore, the application of the antimicrobial agents into implant surfaces to prevent implant-associated infection has attracted much attention. Scientific papers have shown that inorganic antibacterial metal elements (e.g., Ag, Cu, Zn) can be introduced into implant surfaces with the addition of metal nanoparticles or m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 111 publications
1
38
0
Order By: Relevance
“…Such molecules may prevent the adhesion of NPs to the cell barrier, and even regulate the exchange flow of ions through the bacterial cell membrane, thus reducing the killing effect of the NPs [40,73]. However, NPs are able to interact with the bacterial cell membrane, since the NP surface atoms can also bind with the negatively charged carboxyl and phosphate groups present in the bacterial cell membrane [25,40,74].…”
Section: Membrane Damagementioning
confidence: 99%
“…Such molecules may prevent the adhesion of NPs to the cell barrier, and even regulate the exchange flow of ions through the bacterial cell membrane, thus reducing the killing effect of the NPs [40,73]. However, NPs are able to interact with the bacterial cell membrane, since the NP surface atoms can also bind with the negatively charged carboxyl and phosphate groups present in the bacterial cell membrane [25,40,74].…”
Section: Membrane Damagementioning
confidence: 99%
“…Several studies have focused on the incorporation of Zn onto a Ti surface by MAO treatment [58][59][60][61][62][63][64]. Hu et al [59], Zhang et al [61], Zhang et al [62] and Du et al [63] reported that Zn-incorporated TiO 2 coatings showed good antibacterial activity against both Escherichia coli (E. coli) and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…To preserve the superior mechanical properties of Ti alloys' bulk and improve the hardness and wear resistance of their surface, surface modification is one of the methods often used. Surface modification techniques may include micro-arc oxidation [7], ion implantation [8], plasma spraying [9], physical vapor deposition [10], the sol-gel technique [11], and plasma-assisted chemical vapor deposition [12]. In recent years, the laser cladding process (as an advanced and promising surface modification technique) has been used to prepare coatings to improve tribological property or medical biocompatibility of titanium alloys [13].…”
Section: Introductionmentioning
confidence: 99%